214k views
1 vote
Solve in Multi Step (Show work)
-2x + 5 = -6

User Fuzic
by
6.0k points

2 Answers

3 votes

Answer: 5.5 is your answer.

Explanation:

1) -2x + 5 -5 = -6 -5 <------Subtract 5 from 5 and 5 from -6.

2) -2/-2 x = -11/-2 <---------------Now divide -2 by -2 and divide -2 by -11.

3) x = 5.5 <-------------And this is your answer.

Hope this helped! Have a great day! :).

User Manish J
by
6.1k points
5 votes

Answer:

5.5

Explanation:

-2x + 5 = -6

subtract -5 from -6 then divide by -2

i hope i explained it well.

User Willem Mulder
by
6.4k points